The role of snail aestivation in transmission of schistosomiasis in changing climatic conditions. Issue 2 (27th May 2016) - Rubaba, O; Chimbari, MJ; Mukaratirwa, S
Abstract : Schistosomiasis vector snails are subjected to extreme seasonal changes, particularly in ephemeral rivers and lentic waterbodies. In the tropics, aestivation is one of the adaptive strategies for survival and is used by snails in times of extremely high temperatures and desiccation. Aestivation therefore plays an important role in maintaining the transmission of schistosomiasis. This review assesses the possible impacts of climate change on the temporal and spatial distribution of schistosomiasis-transmitting snails with special emphasis on aestivation, and discusses the effect of schistosome infection on aestivation ability. The impacts of parasite development on snails, as well as physiological changes, are discussed with reference to schistosomiasis transmission. This review shows that schistosome-infected snails have lower survival rates during aestivation, and that those that survive manage to get rid of the infection. In general, snail aestivation ability is poor and survival chances diminish with time. Longer dry periods result in fewer, as well as uninfected, snails. However, the ability of the surviving snails to repopulate the habitats is high.